The Battle of Student Ideology at State Islamic Higher Education Institution: Student Movement Activism for Liberation and Student Element Resistance - As’ad, As’ad; Fridiyanto, Fridiyanto; Rafi’i, Muhammad (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This paper seeks to analye the ideological battle between Hizbut Tahrir Indonesia (HTI) through Gerakan Mahasiswa Pembebasan (Gema Pembebasan; the Liberation Student Movement) and intra-campus (DEMA; Student Executive Council) and extra-campus student associations at State Islamic Higher Education (PTKIN). The main article’s objectives are what issues often propagated by HTI activists are; and what the reactions and resistances of opposite student activists towards HTI’s ideology are. The research method used is qualitative, with a multi-case design. Data collection was carried out directly by observing and in-depth interviewing informants from various elements of the student movement; HTI activists, student presidents of DEMA and other administrators, as well as student activists either through direct or phone interviews. The results of the study showed that Gema Pembebasan activists as the underbow of HTI had militancy and high discipline to promote ideology and struggled to uphold the caliphate. HTI activists campaigned the Khilafah Islamiyah ideology and concept through various media and intellectual activities. In propaganda scheme, HTI activists always make tag line campaigns such as “Democracy is Haram”, “Khilafah Islamiyah is the solution”, and “Stop the Secular System”. This article also concluded that the provocative actions of Gema Pembebasan activists have generated a number of resistance from the opposite activists. The intra-and extra-campus organizations activists attempt to fight HTI’s ideological propaganda through various strategies, such as intellectualism and intimidation. However, the resistance power was no longer found since HTI was dissolved by the Government. Tulisan ini bertujuan mendiskusikan pertarungan ideologi antara aktivis Hizbut Tahrir Indonesia (HTI) melalui Gerakan Mahasiswa Pembebasan (Gema pembebasan) dengan organisasi mahasiswa intra kampus (DEMA; Dewan Eksekutif Mahasiswa) dan ekstra kampus di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Pertanyaan utama artikel ini adalah isu apa saja yang sering dipropagandakan aktivis HTI; dan apa saja reaksi serta resistensi aktivis mahasiswa yang kontra dengan ideologi HTI. Metode penelitian yang digunakan adalah kualitatif, dengan rancangan multikasus. Pengumpulan data dilakukan secara langsung dengan mengamati dan mewawancarai secara mendalam informan dari berbagai elemen gerakan mahasiswa; aktivis HTI, presiden mahasiswa DEMA dan pengurusnya, dan aktivis mahasiswa baik secara langsung maupun via handphone. Hasil penelitian menemukan bahwa aktivis Gema Pembebasan sebagai sayap organisasi (underbow) HTI memiliki militansi dan disiplin tinggi untuk mempromosikan ideologi dan perjuangan menegakkan khilafah. Aktivis HTI mengkampanyekan ideologi dan konsep Khilafah Islamiyah melalui berbagai media cetak maupun kegiatan intelektual. Dalam aktivitas propaganda, aktivis HTI selalu membuat tag line kampanye seperti “Demokrasi itu Haram”, “Khilafah Islamiyah Solusi”, dan “Hentikan Sistem Sekuler”. Artikel ini juga menyimpulkan bahwa tindakan provokatif aktivis Gema Pembebasan menuai banyak reaksi resisten dan perlawanan dari aktivis penentang HTI. Aktivis organisasi intra dan ekstra kampus mencoba melawan dakwah ideologi HTI melalui berbagai cara seperti cara intelektualisme bahkan intimidasi. Namun, daya resistensi tidak ditemukan lagi setelah HTI dibubarkan oleh Pemerintah